Analisis Pemenuhan Standar Nasional Pelayanan Kesehatan Peduli Remaja (SN-PKPR) pada Puskesmas Mampu Laksanan PKPR di Kota Jambi Tahun 2020 - Verawati Pulungan; Agustin Kusumayati (Syntax Corporation Indonesia, 2021)
Standar Nasional Pelayanan Kesehatan Peduli remaja (PKPR) is a program by Kementrian Kesehatan Indonesia as an effort to overcome the increasing problems in adolescence which is applied to health centers capable of implementing PKPR by using a PKPR National Standard. However, from the 2018 data there is still an increase in adolescent risk behavior so the research was carried out to describe the achievement of meeting the National Standards for Youth Care Health Services at Puskesmas that are able to be like PKPR in Jambi City. This research is a descriptive study with a quantitative approach using a cross-sectinal design. The sample in the study was the same as the population, namely all health centers in Jambi, totaling 20 health centers. The data in this research are primary and secondary data taken by interview using a questionnaire. The results showed that the achievement of the achievement of the fulfillment of SN-PKPR in Puskesmas capable of implementing PKPR in Jambi City has been running quite well, with the highest level of fulfillment being optimal, namely 70% and 30% at the minimum level and no Puskesmas in Jambi City has reached the Plenary fulfillment. There needs to be coordination between the Government, the Jambi provincial health office and the Puskesmas in implementing and evaluating the implementation of the PKPR program